Traditional Borneo Game in Improving Student Character : Changes in Social Behavior - Muhammad Ramli Buhari; Muhammad Rifai; Hendry Ismawan; Hamdiana (UNIB Press, 2023)
The purpose of this research is to reveal the result of an experiment of a traditional game native to Kalimantan in improving students' character: changes in social behavior. The method used is the experimental method: participants, 60 junior high school students aged 12 to 13 years. The research instrument used a questionnaire regarding students' social behavior. The data processing and analysis technique used the t-test analysis technique. From the test results, it is obtained that t count = 7.82 and p = 0.001. The test results showed significant differences in social behavior between the experimental and control groups. The conclusion from the results of this study is that the traditional game of Borneo Asen Naga (AN) has a significant influence on the formation of students' social behavior. The development of social behavior that is most visible from the treatment results in this traditional game is the aspect of cooperation. Meanwhile, the male sample group showed better motor development than the female group motor behavior.